2018
DOI: 10.1186/s12974-018-1243-0
|View full text |Cite
|
Sign up to set email alerts
|

Splenic involvement in umbilical cord matrix-derived mesenchymal stromal cell-mediated effects following traumatic spinal cord injury

Abstract: BackgroundThe spleen plays an important role in erythrocyte turnover, adaptive immunity, antibody production, and the mobilization of monocytes/macrophages (Mφ) following tissue injury. In response to trauma, the spleen initiates production of inflammatory cytokines, which in turn recruit immune cells to the inflamed tissue, exacerbating damage. Our previous work has shown that intravenous mesenchymal stromal cell (MSC) infusion has potent immunomodulatory effects following spinal cord injury (SCI), associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…The fact that conditioned media derived from HUCPVCs did not rescue degeneration in OGD cultures suggests that an injury cue is required to produce factors that promote axon survival. This notion is supported by our in vivo findings whereby HUCPVCs improved cortical axon morphology despite evidence indicating that many MSCs get trapped in peripheral organs, such as the lung, liver, and spleen [8,54,55]. At 24 h, although not quantified, we found the systemically injected PKH26-labeled cells in the lungs and spleen but not in the brain.…”
Section: Discussionsupporting
confidence: 77%
“…The fact that conditioned media derived from HUCPVCs did not rescue degeneration in OGD cultures suggests that an injury cue is required to produce factors that promote axon survival. This notion is supported by our in vivo findings whereby HUCPVCs improved cortical axon morphology despite evidence indicating that many MSCs get trapped in peripheral organs, such as the lung, liver, and spleen [8,54,55]. At 24 h, although not quantified, we found the systemically injected PKH26-labeled cells in the lungs and spleen but not in the brain.…”
Section: Discussionsupporting
confidence: 77%
“…However, we were unable to find any transplanted cells at the lesional and peri‐lesional area. Strikingly, our lab and others have recently reported that, while systemically infused MSCs distribute mainly to the lung and spleen, they continue to exert therapeutic effects on the local spinal cord milieu. In these studies, the authors propose two possible mechanisms through which the remotely distributed MSCs exert their therapeutic effect: (a) MSCs serve as cellular decoys, where the immune system targets these exogeneous human cells instead of endogenous cells, thus minimizing damage; and (b) MSCs release anti‐inflammatory cytokines in the spleen, such as IL10, and impact immune cell recruitment and phenotype.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have identified MSC-like cells in human UC tissue, but the cells were not well defined (16)(17)(18)(19)(20)(21). Unlike previously isolated UC tissue stromal cells, which have been primarily derived from Wharton's jelly (17)(18)(19)21), we focused on isolating arterial-derived stromal cells since perivascular cells around arteries have been shown to regulate hematopoietic cell production during development (24). Using flow cytometry, we found a population of CD51 + PDGFRα + arterial-derived stromal cells, termed cord-tissue Mesenchymal Stromal Cells (cMSCs), which were nonerythroid (CD235a -), nonendothelial (CD31 -), and nonhematopoietic (CD45 -).…”
Section: Resultsmentioning
confidence: 98%
“…Since cord blood-derived CD34 cells have been shown to differentiate into megakaryocytes with high efficiency compared with those isolated from peripheral blood and BM, we focused on identifying a compatible stromal cell from human UC tissue (23). Previous studies have identified MSC-like cells in human UC tissue, but the cells were not well defined (16)(17)(18)(19)(20)(21). Unlike previously isolated UC tissue stromal cells, which have been primarily derived from Wharton's jelly (17)(18)(19)21), we focused on isolating arterial-derived stromal cells since perivascular cells around arteries have been shown to regulate hematopoietic cell production during development (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation